The role of small- and medium-sized enterprises in the Dutch economy: An analysis using an extended supply and use table - Stephen Chong; Rutger Hoekstra; Oscar Lemmers; Ilke Van Beveren; Marcel van den Berg; Ron van der Wal; Piet Verbiest (Journal of Economic Structures, 2019)
Firm size is increasingly acknowledged as an important factor for (macro-)economic policy. It is known that the overall importance of small- and medium-sized enterprises (SMEs) is different relative to large multinationals in terms of their impact on economic growth, exports and innovation. Yet empirical evidence to substantiate the role of firms of different sizes is rare. To tackle this problem, we develop a novel approach by extending the Dutch supply-use framework to firm size. We utilize firm-level data to construct a purpose-built supply-use table distinguishing between SMEs and large enterprises and derive an extended input-output table. In doing so, we adopt a more evolved definition of SMEs, accounting for the fact that small firms may be subsidiaries of large (multinational) enterprise groups. The analysis shows that due to their function as suppliers, SMEs benefit much more from Dutch exports to foreign markets than the traditional export figures show. SMEs are less dependent on imports than large enterprises. This might be detrimental to the competitiveness of SMEs if they do not fully appreciate the benefits of sourcing internationally in terms of cheaper or higher quality inputs. The paper shows the policy relevance of macroeconomic statistics which distinguish firm size.
Keywords: 330; Exports; SME; GDP supply-use tables; Input-output table; Input-output analysis; Firm heterogeneity